2004
DOI: 10.1128/aem.70.1.550-557.2004
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Activity at −2 to −20°C in Arctic Wintertime Sea Ice

Abstract: Arctic wintertime sea-ice cores, characterized by a temperature gradient of ؊2 to ؊20°C, were investigated to better understand constraints on bacterial abundance, activity, and diversity at subzero temperatures. With the fluorescent stains 4,6-diamidino-2-phenylindole 2HCl (DAPI) (for DNA) and 5-cyano-2,3-ditoyl tetrazolium chloride (CTC) (for O 2 -based respiration), the abundances of total, particle-associated (>3-m), freeliving, and actively respiring bacteria were determined for ice-core samples melted at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
296
4
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(313 citation statements)
references
References 50 publications
11
296
4
2
Order By: Relevance
“…High degradation rates could be found in the field for several other low pour-point oils, although in some cases oil composition could lead to divergent results. In ice-covered areas however, where temperature in first-year ice varies between -2 and -20°C (Junge et al 2004), degradation rates would potentially be much lower than what was observed in ice microcosms because only 39% of the ITOPF-classified oils would exhibit liquid characteristics below -15°C. At temperature as low as -25 °C in multi-year ice (Perovich & Elder 2001), biodegradation rates would be negligible, if not null, because most oils will solidify (ITOPF 2011) and because very cold ice has little brine volume fraction and thus, fewer microhabitats to support an active bacterial community (Deming 2010).…”
Section: Factors Governing Hydrocarbon Degradation In Ice-covered Arcmentioning
confidence: 96%
See 1 more Smart Citation
“…High degradation rates could be found in the field for several other low pour-point oils, although in some cases oil composition could lead to divergent results. In ice-covered areas however, where temperature in first-year ice varies between -2 and -20°C (Junge et al 2004), degradation rates would potentially be much lower than what was observed in ice microcosms because only 39% of the ITOPF-classified oils would exhibit liquid characteristics below -15°C. At temperature as low as -25 °C in multi-year ice (Perovich & Elder 2001), biodegradation rates would be negligible, if not null, because most oils will solidify (ITOPF 2011) and because very cold ice has little brine volume fraction and thus, fewer microhabitats to support an active bacterial community (Deming 2010).…”
Section: Factors Governing Hydrocarbon Degradation In Ice-covered Arcmentioning
confidence: 96%
“…In winter, chances are that sea ice would be impermeable because the temperature can drop below -5 °C (Junge et al 2004). This means that oil spilled on the ice cover would not percolate and be in contact with bottom-ice bacterial communities, thereby limiting biodegradation.…”
Section: Factors Governing Hydrocarbon Degradation In Ice-covered Arcmentioning
confidence: 99%
“…The amount of particulate material correlated positively with microbial abundance and functional diversity, whereas CaCO 3 concentration corresponded with bacterial phylogenetic diversity. The beneficial role of particulates for microbial activity have been previously recorded for polar aquatic habitats (Junge et al 2004).…”
Section: Significant Environmental Controlsmentioning
confidence: 99%
“…Junge et al showed that many microorganisms in sea ice occupy brine channels (2) and that many in lake ice occupy veins (3). Mader et al (4) showed that both bacteria and fluorescent beads added to water used to make ice are rejected from the solid phase and incorporated into liquid veins, provided that they are small enough to fit, whereas beads larger than the vein diameter are frozen into solid ice.…”
mentioning
confidence: 99%